Gender Discrimination In The Drama Series The Exchange: A Sara Mills Critical Discourse Analysis: At-Tamyīz al-Jindarī fī al-Musalssal ad-Dirāmī "At-Tabādul": Taḥlīl al-Khiṭāb an-Naqdī li-Sārā Mīlz - Yuni Syakila Wardah; Misbahus Surur (An-Nahdah Al-'Arabiyah, 2025)
The Exchange is a Netflix drama series inspired by true events experienced by two Kuwaiti women. The two women threw themselves into the male-dominated Kuwaiti stock market. The purpose of this study is to analyze the position of the actor who is the subject of the storytelling, the object being told, and the position of the audience with Sara Mills' critical discourse analysis model through scenes of the film that are considered representative. This research is intended to find the forms of discrimination experienced by the main female character in the drama series The Exchange. This type of research is descriptive qualitative using Sara Mills' critical discourse analysis. The main data source is the drama series The Exchange episode 1 to 5. The research data is in the form of scene images and dialog in the drama series that show forms of discrimination against women. Data analysis in this study used three stages, including; (1) data reduction, (2) data presentation, and (3) conclusion drawing. The results showed that there are 4 forms of discrimination experienced by the main female character in the workplace, including 1) marginalization with 3 scenes; 2) subordination with 2 scenes; 3) stereotyping with 2 scenes; and 4) workload with 1 scene. Each scene has actors who occupy the position of the subject of the storytelling, the object being told, and the position of the audience. The Exchange هو و مسلسل درامي من إنتاج نتفليكس مستوحى من أحداث حقيقية عاشتها سيدتان كويتيتان. ألقت المرأتان بنفسيهما في سوق الأسهم الكويتية التي يهيمن عليها الرجال. والغرض من هذه الدراسة هو تحليل موقف الممثل الذي هو موضوع الحكاية، والموضوع الذي يتم سرده، وموقف الجمهور من خلال نموذج تحليل الخطاب النقدي لسارة ميلز من خلال مشاهد الفيلم التي تعتبر تمثيلية. يهدف هذا البحث إلى إيجاد أشكال التمييز التي تعاني منها الشخصية الأنثوية الرئيسية في المسلسل الدراميThe Exchange .  هذا النوع من البحث نوعي وصفي باستخدام تحليل الخطاب النقدي لسارة ميلز. مصدر البيانات الرئيسي هو المسلسل الدراميThe Exchange من الحلقة 1 إلى 5. وتتمثل بيانات البحث في شكل صور مشاهد وحوار في المسلسل الدرامي تظهر أشكال التمييز ضد المرأة. واستخدم في تحليل البيانات في هذه الدراسة ثلاث مراحل، منها: (1) اختزال البيانات، (2) عرض البيانات، (3) استخلاص النتائج. أظهرت النتائج أن هناك 4 أشكال من التمييز التي تتعرض لها الشخصية النسائية الرئيسية في مكان العمل، منها: (1) التهميش بـ3 مشاهد، (2) التبعية بمشهدين، (3) التنميط بمشهدين، (4) عبء العمل بمشهد واحد. يضم كل مشهد ممثلين يحتل كل منهم موقع الفاعل في الحكاية، والمفعول به الذي يتم سرده، وموقع الجمهور. The Exchange merupakan salah satu serial drama Netflix terinspirasi kejadian nyata yang pernah dialami oleh dua Wanita Kuwait. Dua wanita tersebut menceburkan diri ke pasar saham Kuwait yang didominasi kaum laki-laki. Tujuan penelitian ini adalah untuk menganalisis posisi aktor yang menjadi subjek pencerita, objek yang diceritakan, dan posisi penonton dengan model analisis wacana kritis Sara Mills melalui scene-scene film yang dianggap mewakili. Penelitian ini dimaksudkan untuk menemukan bentuk-bentuk diskriminasi yang dialami oleh tokoh utama perempuan dalam serial drama The Exchange. Jenis penelitian ini adalah deskriptif kualitatif menggunakan analisis wacana kritis Sara Mills. Sumber data utama yakni serial drama The Exchange episode 1 sampai 5. Data penelitian berupa gambar scene dan dialog dalam serial drama yang menunjukkan bentuk-bentuk diskriminasi perempuan. Analisis data dalam penelitian ini menggunakan tiga tahap, di antaranya; (1) reduksi data, (2) penyajian data, dan (3) penarikan kesimpulan. Hasil penelitian menunjukkan ada 4 bentuk diskriminasi yang dialami oleh tokoh utama perempuan di tempat kerja, di antaranya 1)  marginalisasi dengan 3  scene; 2) subordinasi dengan 2 scene; 3) stereotip dengan 2 scene; dan 4) beban kerja dengan 1 scene. Masing-masing scene mempunyai aktor yang menempati posisi sebagai subjek pencerita, objek yang diceritakan, dan dan posisi penonton.